Pd(II)‐Functionalized Polymeric Shell Encapsulated on Magnetite Nanocatalysts for C−C Coupling Reactions. Issue 33 (5th September 2022) - Rathod, Prakash B.; Ajish Kumar, K. S.; Pratap Singh, Mahendra; Athawale, Anjali A.; Pandey, Ashok K.
Abstract: A polymeric network grafted on the magnetite nanoparticles (Fe3 O4 @PAA−PPh3 ) were found to aggregate in the form a cotton‐ball like morphology, which exhibited a good loading of Pd(II) generally used as homogeneous catalyst in many coupling reactions. To prepare the Fe3 O4 @PAA−PPh3 nanoplatform for loading Pd(II), Fe3 O4 nanoparticles (NPs) functionalized with amines were coupled to polyacrylic acid (PAA), polyethylene amine (PEI) and triphenyl phosphine (PPh3 ) sequentially using the HBTU‐DIEA coupling method. The Pd(II)‐loaded Fe3 O4 @PAA−PPh3 catalyst showed better activity toward the representative Mizoroki‐Heck type coupling reactions. The catalytic activity of Fe3 O4 @PAA−PPh3 loaded with palladium was compared with the available homogenous and heterogeneous catalyst systems. This comparison seemed to suggest that Pd(II)‐loaded Fe3 O4 @PAA−PPh3 had higher turnover frequency, which could be a potential alternative to the existingnanoplatforms for loading homogeneous catalysts in terms of not only better turnover number and turnover frequency but also improved recyclability. Abstract : A triphenylphosphine functionalized polymer encapsulation on magnetite nanoparticles has been developed to complex with Pd 2+ ions for loading homogeneous catalyst which exhibits higher turnover number and frequency in catalyzing Mizoroki‐Heck type C−C coupling with recyclability.